1997
DOI: 10.1046/j.1365-2958.1997.5141874.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an exported protease from Shiga toxin‐producing Escherichia coli

Abstract: SummaryThe gene for a novel, high molecular weight protein secreted by Shiga toxin-producing Escherichia coli (STEC) has been cloned, sequenced and characterized with respect to its activity. This gene, designated pssA, is localized on the large plasmid that also harbours the STEC haemolysin operon. Sequencing of a region comprising 10 630 nt revealed that the sequences flanking the pssA gene are composed of several remnants of different insertion elements. The PssA protein is produced as a 142 kDa precursor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 47 publications
2
90
0
2
Order By: Relevance
“…At the same time, Djafari et al (1997) described a protease d ' ' terme protease secreted by STEC' A or PssA, which appears to be the same as that reported by Brunder et al (1997). This protease was encoded on the espP gene located on the large plasmid carried by 0157 VTEC and was a 104 kDa protein.…”
Section: Serine Protease Production By Vtecsupporting
confidence: 61%
“…At the same time, Djafari et al (1997) described a protease d ' ' terme protease secreted by STEC' A or PssA, which appears to be the same as that reported by Brunder et al (1997). This protease was encoded on the espP gene located on the large plasmid carried by 0157 VTEC and was a 104 kDa protein.…”
Section: Serine Protease Production By Vtecsupporting
confidence: 61%
“…EspP (also known as PssA) is considered by some authors to be a cytotoxin because it causes cytotoxic effects on Vero cells (38). We found that incubation of HeLa cell monolayers with bacteria-free ropes or EspP monomers for 24 h led to cell rounding (Fig.…”
Section: Biochemical and Physical Properties Of The E Coli Ropes-cd mentioning
confidence: 72%
“…People naturally or experimentally infected with EPEC or EHEC develop antibodies against EspC or EspP, respectively (38,43). We found that a pool of sera obtained from HUS patients reacted with the rope-forming EspP protein, whereas normal human sera did not show any reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, almost simultaneously Brunder et al (49) described EspP (for "extracellular serine protease plasmid-encoded") and Djafari et al (106) described PssA (for "protease secreted by STEC") in EHEC O157:H7 and Shiga-toxin producing E. coli (STEC) O26:HϪ, respectively. These proteins are identical, are encoded on the large virulence plasmids, and represent the major extracellular proteins of both organisms.…”
Section: Serine Protease Autotransporters Of the Enterobacteriaceaementioning
confidence: 99%
“…On the other hand, both proteins are highly im- (49,106). Interestingly, different biological activities were described for EspP and PssA.…”
Section: Serine Protease Autotransporters Of the Enterobacteriaceaementioning
confidence: 99%